Designing Microfluidic Devices to Sort Haematopoietic Stem Cells Based on Their Mechanical Properties. (5th September 2019) - Du, Mingming; Kavanagh, Dean; Zhang, Zhibing; Kalia, Neena
Abstract : Aim . Few haematopoietic stem cells (HSCs) injected systemically for therapeutic purposes actually reach sites of injury as the vast majority become entrapped within pulmonary capillaries. One promising approach to maintain circulating HSC numbers would be to separate subpopulations with smaller size and/or greater deformability from a heterogeneous population. This study tested whether this could be achieved using label-free microfluidic devices. Methods . 2 straight (A-B) and 3 spiral (C-E) devices were fabricated with different dimensions. Cell sorting was performed at different flow rates after which cell diameter and stiffness were determined using micromanipulation. Cells isolated using the most efficient device were tested intravitally for their ability to home to the mouse injured gut. Results . Only straight Device B at a high flow rate separated HSCs with different mechanical properties. Side outlets collected mostly deformable cells (nominal rupture stress/σ R = 6.81   kPa ; coefficient of variation/CV = 0.31 ) at a throughput of2.3 × 10 5 cells/min. All spiral devices at high flow rates separated HSCs with different stiffness and size. Inner outlets collected mostly deformable cells in Devices C (σ R = 25.06   kPa ;CV = 0.26 ), D (σ R = 22.21   kPa ;CV = 0.41 ), and E (σ R = 29.26   kPa ;CV = 0.27 ) at throughputs of2.3 × 10 5 cells/min, 1.5 × 10 5 cells/min, and1.6 × 10 5 cells/min, respectively. Since Device C separated cells with higher efficiency and throughput, it was utilized to test the homing ability of separated cells in vivo . Significantly more deformable cells were observed trafficking through the injured gut—interestingly, increased retention was not observed. Conclusion . This study applied microfluidics to separate subpopulations from one stem cell type based on their intrinsic mechanical heterogeneity. Fluid dynamics within curved devices most effectively separated HSCs. Such devices may benefit cellular therapy.